Antigen Production in Plant to Tackle Infectious Diseases Flare Up: The Case of SARS - Demurtas, Olivia C.; Massa, Silvia; Illiano, Elena; De Martinis, Domenico; Chan, Paul K. S.; Di Bonito, Paola; Franconi, Rosella (Frontiers in Plant Science, 2016)
Severe Acute Respiratory Syndrome (SARS) is a dangerous infection with pandemic potential. It emerged in 2002 and its aetiological agent, the SARS Coronavirus (SARS-CoV), crossed the species barrier to infect humans, showing high morbidity and mortality rates. No vaccines are currently licensed for SARS-CoV and important efforts have been performed during the first outbreak to develop diagnostic tools. Here we demonstrate the transient expression in Nicotiana benthamiana of two important antigenic determinants of the SARS-CoV, the nucleocapsid protein (N) and the membrane protein (M) using a virus-derived vector or agro-infiltration, respectively. For the M protein, this is the first description of production in plants, while for plant-derived N protein we demonstrate that it is recognized by sera of patients from the SARS outbreak in Hong Kong in 2003. The availability of recombinant N and M proteins from plants opens the way to further evaluation of their potential utility for the development of diagnostic and protection/therapy tools to be quickly manufactured, at low cost and with minimal risk, to face potential new highly infectious SARS-CoV outbreaks.